Vaginal Progesterone Gel versus Intramuscular Progesterone for Luteal Phase Support in Suboptimal Responders Undergoing Assisted Reproductive Cycles - Hasan Ulubaşoğlu; Kadir Bakay; Ali Yavuzcan; Davut Güven; Şafak Hatırnaz; Michael H. Dahan (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: The purpose of this research is to compare the efficacy of 8% micronized vaginal progesterone gel (VAG) at 180 mg daily versus intramuscular progesterone (IMP) in oil at 100 mg daily for luteal phase support (LPS) after fresh single embryo transfer (SET) in Patient-Oriented Strategies Encompassing Individualized Oocyte Number (POSEIDON) Group 1b patients, and to ascertain whether the type of LPS predicts live birth in these patients. Methods: A total of 2420 assisted reproductive technology (ART) cycles performed in Ondokuz Mayıs University IVF Unit were analysed retrospectively. The data of POSEIDON Group 1b (unexpected suboptimal responders) who underwent antagonist in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles were included. All patients were categorized into groups according to the form of LPS, specifically VAG and IMP. Pregnancy, clinical pregnancy rate (CPR), live birth rate (LBR), spontaneous abortion rate and predictors of live birth (age, infertility duration, body mass index (BMI), type of progesterone used for luteal support, serum day 3 estradiol, serum progesterone on the day of human coryonic gonadotrophin (HCG), total duration of induction, serum estradiol on the day of HCG, the total number of oocytes retrieved, number of mature oocytes obtained, average gonadotropin dose per day, total gonadotropin dose administered and total number of embryos retrieved) were analyzed. Results: There was no statistically significant difference between the micronized VAG and IMP groups in terms of age (31 (23–35) vs. 27 (23–35), p = 0.319). There were no statistically significant differences in pregnancy outcomes between the two groups concerning CPR per transfer (70.6% vs. 75.6%; p = 0.364), ongoing pregnancy per cycle (36.2% vs. 39.5%; p = 0.577), and LBR per cycle (34.4% vs. 36.1%; p = 0.785). The spontaneous abortion rates (36.2% vs. 36.8%; p = 0.921) were similar between VAG and IMP groups. The type of LPS did not emerge as a parameter predicting pregnancy (odds ratio (OR): 0.718, 95% confidence interval (95% CI): 0.652–1.313, p = 0.451), clinical pregnancy (OR: 0.598, 95% CI: 0.592–1.289, p = 0.562) and live birth (OR: 0.802, 95% CI: 0.661–1.202, p = 0.580). The logistic regression analysis aimed at assessing the influence of confounding factors, namely age, BMI, and duration of infertility on pregnancy rate, CPR and LBR, did not reveal statistically significant results (p > 0.05). Conclusions: VAG 180 mg daily provide similar pregnancy outcomes compared to 100 mg daily IMP in POSEIDON Group 1b patients undergoing antagonist fresh IVF/ICSI cycles.